DEVELOPING STRATEGY FOR ELECTRICAL & AUTOMATION SYSTEM INTEGRATOR COMPANY FOR FACING FUTURE BUSINESS UNCERTAINTY - Dody Budi Satriyo; Utomo Sarjono Putro (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
PT Mitra is a private limited company that has been around since 1996. PT Mitra specialize in electrical and automation and has many clients in state owned company like PT. Pertamina, PT Semen Indonesia, PT PLN, PT. Biofarma and private owned company like PT. British Petroleum Berau, PT Indocement, etc. In the last four years, PT. Mitra revenue has growth exponentialy. This made the company growth into a big scale company that is rated from their revenue, employee and capital. The sudden growth of PT. Mitra is supported by their cyclical revenue which can create a problem if PT. Mitra owner and management cannot manage the company well. The scenario planning method try to give some alternative vision and how should the owner and management react by developing their strategy. The scenario planning in this study is design for five years duration and the strategy will be developed using TOWS analysis to create a multiple strategy for each scenario.